1976
DOI: 10.1139/v76-365
|View full text |Cite
|
Sign up to set email alerts
|

The dependence on wavelength of 13C isotope effects in photolysis of aqueous solutions of ferrie oxalate

Abstract: The formation of carbon dioxide by photolysis of aqueous solutions of ferric oxalate is accompanied by carbon isotopic fractionation. 12C appears preferentially in the evolved CO2, but the isotope effect depends markedly on the wavelength of the light used. Fractionation is essentially zero (k12/k13 = 1.001) at 366 nm, and increases with wavelength, reaching 1.050 at 520 nm. It is proposed that this variation of isotopic discrimination arises from the differing properties of the excited levels formed by photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…At such a higher excitation state, it may be possible that electron transfer or spin crossover might be more-dominant than dissociation. The 13 C isotope effect has been observed in the 366−520 nm range and is found to depend remarkably on the excitation energy . This isotope is not found in the shorter than 366 nm region.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At such a higher excitation state, it may be possible that electron transfer or spin crossover might be more-dominant than dissociation. The 13 C isotope effect has been observed in the 366−520 nm range and is found to depend remarkably on the excitation energy . This isotope is not found in the shorter than 366 nm region.…”
Section: Resultsmentioning
confidence: 95%
“…Photochemistry of Ferrioxalate. Since Draper suggested that the Fe(III) to Fe(II) redox reaction may find applications in photometry, the redox reaction of ferrioxalate solution has been studied widely. The ferrioxalate redox reaction has also been used as a precise actinometer, and its photochemistry has been studied by several techniques including flash photolysis and electroanalysis. ,,, It is generally accepted 4-7 that light induces electron transfer that reduces the Fe(III)(C 2 O 4 ) complex to the Fe(II) complex with the overall photoreaction written as: 5 …”
Section: Introductionmentioning
confidence: 99%
“…The systematic increase of δ 13 C values with f 44 is strong evidence for the cumulative SOA associating with precursor oxidation found by laboratory studies. 22−24 The more conversion of volatile organic compounds (VOCs) to particulate carboxylate increases f 44 and 13 C content in the product phase, such as SOA. Such a systematic trend was first observed in ambient measurements of δ 13 C values of LV-WSOC at a background site 7 but not in the urban site.…”
Section: Resultsmentioning
confidence: 99%
“…The different δ 13 C values between the two sites may be explained by the addition of local LV-WSOC with different δ 13 C at Fukuoka. Isotope fractionation(s) accompanied by different chemical reactions in the condensed phase of LV-WSOC at Fukuoka cannot be the explanation for this shift because the chemical reactions resulting in the release of volatile carbonaceous products, such as carbon dioxide, have normal isotope fractionations, consequently shifting δ 13 C of residual LV-WSOC to a heavier composition. This trend was further investigated using an end-member mixing analysis (EMMA) in subsection .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation